Image Constructıon And Image Levels In Bahaettın Karakoç's Poems - Şahin, Veysel; Sığınır, Emine (İbrahim Halil TUĞLUK, 2025)
Bahaettin Karakoç, known as the "White-Haired White Eagle", one of the leading poets of Turkish poetry after the Republic, has been remembered for his original poetry universe. He pushed the boundaries of language, created new connotative values and increased the meaning value of his poems. This situation has given a different dimension to his poems with his unique (n) poetry perception and unique style. The poet, who has a wide vocabulary, has deepened the meaning universe of his poems with his symbolic designs. The poet, whose poems are lyrical on one side and thought-heavy on the other, aims to convey them with the symbols he creates. Therefore, it is inevitable to encounter a rich set of symbols in his poems. The symbols and fiction of Bahaettin Karakoç's poems reveal the rich, diverse and multi-layered symbols and image levels in his poems. It allows to re-grasp the values of the poet and the aspects reflected in the objects. As a matter of fact, people attribute new meaning values to objects and concepts with the returns of culture, tradition and history. And this happens with the help of icons. The symbols in Karakoç's poems open up to the individual, the traditional and the universal. Symbols integrate with the language and create new designs. In Karakoç's poems, symbols formed by elements of nature appear as religious symbols, cultural and traditional symbols.

Cumhuriyet sonrası Türk şiirinin önde gelen şairlerinden “Ak Saçlı Beyaz Kartal” olarak bilinen Bahaettin Karakoç, özgün şiir evreniyle akıllarda yer etmiştir. Dilin sınırlarını zorlamış, yeni çağrışım değerleri oluşturmuş ve şiirlerinin mana değerini artırmıştır. Bu durum özgü(n) şiir algısı ve kendine has tarzıyla şiirlerine farklı bir boyut kazandırmıştır. Geniş bir kelime hazinesi bulunan şair simgesel tasarılarıyla da şiirlerinin mana evrenini derinleştirmiştir. Şiirlerinin bir yanı lirik diğer tarafı düşünce ağırlıklı olan şair, bunları oluşturduğu simgelerle aktarma gayesindedir. Dolayısıyla onun şiirlerinde zengin simgeler bütünüyle karşılaşmak kaçınılmazdır. Bahaettin Karakoç’un şiirlerinde simge ve kurgusu, onun şiirlerindeki zengin, çeşitli ve çok katmanlı olan simgeleri ve görüntü düzeylerini gözler önüne serer. Şairin değerlerini, objelere yansıyan taraflarını yeniden kavramayı sağlar. Nitekim insanlar nesne ve kavramlara kültürün, geleneğin ve tarihin getirileriyle yeni mana değerleri yükler. Bu da simgeler yardımıyla olur. Karakoç’un şiirlerindeki simgeler bireysel, geleneksel ve evrensele doğru açılır. Simgeler dil ile bütünleşerek yeni tasarılar meydana getirir. Karakoç’un şiirlerinde, tabiata ait unsurlarla oluşan simgeler, dini simgeler, kültürel ve geleneksel simgeler olarak görünmektedir.
BAHAETTİN KARAKOÇ'UN ŞİİRLERİNDE SİMGE KURGUSU VE GÖRÜNTÜ DÜZEYLERİ
Keywords: Modern Turkish Literature in Turkiye Field; Türkiye Sahası Yeni Türk Edebiyatı